The Main Character in Ahmed Kayed’s Novel AL Armalah, “ The Widow “ and the Ways of Depicting Her - Albaharat, Majed; A. Alfayez, Mefleh (Dirasat: Human and Social Sciences, 2022)
This study attempts to tackle the main character, nada Ahmed kayed’s novel ‘ ALArmalah, and examine dimensions: the external materialistic, social and psychological, in addition to the way by which she was depicted. the study concluded that the novelist allows her to convey her dimensions as well as the internal and external characteristics. she played the main part in the development of the fictional action in addition to the role of events in developing this character and clarifying her actions, feeling, passions, thoughts through the inner monologue introspection, and dreaming technique.